Metagenomics Reveals the Microbial Community Responsible for Producing Biogenic Amines During Mustard [Brassica juncea (L.)] Fermentation - Yu, Yangyang; Li, Lu; Xu, Yujuan; Li, Hong; Yu, Yuanshan; Xu, Zhenlin (Frontiers in Microbiology, 2022)
Biogenic amines (BAs) is considered potential hazards produced during fermented food processing, and the production of BAs is closely related to microbial metabolism. In this work, the changes of biogenic amine content were analyzed during mustard fermentation, and microbes and gene abundance responsible for producing BAs revealed by metagenomic analyses. The results showed that cadaverine, putrescine, tyramine, and histamine were generated during mustard fermentation, which mainly accumulates in the first 6 day of fermentation. According to the metagenome sequencing, the predominant genus was Bacillus (64.78 %), followed by Lactobacillus (11.67 %), Weissellas (8.88 %) and Leuconostoc (1.71 %) in the initial fermentation stage (2th day), while Lactobacillus (76.03 %) become to the most dominant genus in the late stage. In addition, the genes abundance of BA-production enzymes was highest in the 2th day, and decreased continuously as fermentation progressed. By tracking the source of the enzyme in the KEGG database, both of Bacillus and Delftia closely correlated to the generation of putrescine. Besides, Bacillus also correlated to the generation of tyramine and spermidine, and Delftia also correlated to the generation of cadaverine and spermine. This study reveals the change of BAs content and microbes involved in biogenic amine formation during mustard fermentation.